2021
DOI: 10.1016/j.bioactmat.2021.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of magnesium ions and simvastatin on attenuation of high-fat diet-induced bone loss

Abstract: Introduction Magnesium (Mg) has a prophylactic potential against the onset of hyperlipidemia. Similar to statin, Mg is recommended as lipid-lowering medication for hypercholesterolemia and concomitantly exhibits an association with increased bone mass. The combination of statin with Mg ions (Mg 2+ ) may be able to alleviate the high-fat diet (HFD)-induced bone loss and reduce the side-effects of statin. This study aimed to explore the feasibility of combined Mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 77 publications
(58 reference statements)
3
18
0
Order By: Relevance
“…showed that 16 weeks of HFD feeding in rodents causes trabecular bone loss but more than 16 weeks of HFD feeding might result in cortical bone damage (74) as observed by us. This indicates that HFD feeding for a longer duration is crucial for cortical damage, as also evidenced in a study by Mansur and coworkers (75).…”
Section: Discussionsupporting
confidence: 77%
“…showed that 16 weeks of HFD feeding in rodents causes trabecular bone loss but more than 16 weeks of HFD feeding might result in cortical bone damage (74) as observed by us. This indicates that HFD feeding for a longer duration is crucial for cortical damage, as also evidenced in a study by Mansur and coworkers (75).…”
Section: Discussionsupporting
confidence: 77%
“…However, the side effects of statins, such as myalgia, myositis, rhabdomyolysis, 6 and liver injury, cannot be ignored, and it may increase the risk of hemorrhagic stroke in patients with cerebrovascular disease. 7 Therefore, it is necessary to develop new bioactive substances. The marine biome contains highly valuable natural resources, and marine polysaccharides have a variety of biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Ca is mainly found stored in native bones, and has an important role to play in regulating angiogenesis and osteogenesis. It has been reported that Ca concentrations at the lower range of 0.2–0.4 mM facilitate osteoblast proliferation and differentiation, whilst higher concentrations tend to favor extracellular matrix mineralization and remodeling [ 33 ]. Ca is reported to regulate bone remodeling via the calcium-sensing receptor (CaSR) and upregulation of insulin-like growth factor II and osteoblastic glutamate.…”
Section: Resultsmentioning
confidence: 99%